The Diverse Oncogenic and Tumor Suppressor Roles of microRNA-105 in Cancer - Li, Jie; Zhang, Zhiyuan; Chen, Fangyu; Hu, Tao; Peng, Wen; Gu, Qiou; Sun, Yueming (Frontiers in Oncology, 2019)
MicroRNAs (miRNAs) are non-coding small RNA molecules that regulate gene expression at the post-transcriptional/translational level. Previous studies found that miRNAs play an important role not only in the normal progress of development, and also their expressions in human diseases are aberrant, including malignancy. With accumulating proofs of miR-105, the complex role of miR-105 is gradually emerging during tumor initiation and progression. miR-105 acts as a tumor suppressor by inhibiting proliferation and invasion, or by promoting tumor initiation and proliferation as an oncogene, depending on the specific tumor context and target genes. In this review, we focus on the characteristics of miR-105 in cancer to better elucidate a variety of deadly tumor. In addition, we discuss transcriptional regulations that may explain the fluctuations in miR-105 expression. This work may provide new ideas for applying miR-105 as a diagnostic and prognostic biomarker.